2020
DOI: 10.1093/ajhp/zxaa008
|View full text |Cite
|
Sign up to set email alerts
|

Improving clinic utilization and workload capture for clinical pharmacy specialists

Abstract: Purpose To assess a quality improvement initiative aimed at improving clinic utilization and encounter and intervention workload capture for clinical pharmacy specialists. This initiative aided in justification of clinical pharmacy services, identification of clinical areas for intervention, and incorporation of all modalities to appropriately document clinical care. Methods In order to objectively demonstrate clinical pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Compared with a single-phase system in which the physician performs all parts of the service, the results showed that the addition of MLSP reduced patient waiting time, patient flow time, and physician service time. Steen et al adjusted the location of workload generation and activities in working days, improving clinic utilization rate and a total number of visits in the clinical pharmacy expert compound group [ 35 ]. The implementation of the intervention shows that pharmaceutical administrators can improve workload and obtain quality care by cooperating with clinical pharmaceutical experts.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with a single-phase system in which the physician performs all parts of the service, the results showed that the addition of MLSP reduced patient waiting time, patient flow time, and physician service time. Steen et al adjusted the location of workload generation and activities in working days, improving clinic utilization rate and a total number of visits in the clinical pharmacy expert compound group [ 35 ]. The implementation of the intervention shows that pharmaceutical administrators can improve workload and obtain quality care by cooperating with clinical pharmaceutical experts.…”
Section: Discussionmentioning
confidence: 99%
“…However, estimating clinical pharmacist FTEs from provider panel size is challenging without considering the patient population and clinical pharmacist's direct patient care and non‐direct patient care responsibilities. Clinical pharmacist panel sizes need to be adjusted to account for the medical complexity of the patient population because of medication management needs, challenges encountered with social determinants of health, scope and intensity of ambulatory pharmacy services provided, and other activities factoring into pharmacist workload (i.e., administrative, scholarship, and teaching duties) 18,20,75,76 …”
Section: Pharmacy Specialty‐specific Commentarymentioning
confidence: 99%
“…Clinical pharmacist panel sizes need to be adjusted to account for the medical complexity of the patient population because of medication management needs, challenges encountered with social determinants of health, scope and intensity of ambulatory pharmacy services provided, and other activities factoring into pharmacist workload (i.e., administrative, scholarship, and teaching duties). 18,20,75,76 Patient panel size for a pharmacy service in the ambulatory care setting may initially be estimated using population health or hospital discharge statistics identifying patients who would benefit from clinical pharmacist-led services (e.g., those targeted at reducing heart failure readmissions or improving quality measures). As previously mentioned, the VHA model offers a strategy for making this estimation.…”
Section: Ambulatory Carementioning
confidence: 99%